Modified Direct Power Controller for Doubly Fed Induction Generator Driven by Wind Energy - Ahmed Hassan Adel, Salama Abo-Zaid, Mahmoud Elwany (International Journal of Advanced Science and Technology, 2020)
This paper presents design and analysis of a direct power controller (DPC) for grid side converter (GSC) of doubly fed induction generator (DFIG) driven by wind energy. DPC consists of switching table, two hysteresis comparators and direct and quadrature current estimator. This paper deals with direct and quadrature current components instead of active and reactive power components for switching table. This paper also proposes a modified DPC using a modified switching table to reduce current and power ripples. This paper gives three control strategies for GSC; pulse width modulation based on vector control, DPC and modified DPC. Matlab Simulink model for 9 MW DFIG wind farm, Simulation results and a comparison between the three strategies are given in this paper.